2020
DOI: 10.21203/rs.2.15865/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel heavy metal resistance gene clusters are present in the genome of Cupriavidus neocaledonicus STM 6070, a new species of Mimosa pudica microsymbiont isolated from heavy-metal-rich mining site soil

Abstract: Background: Cupriavidus strain STM 6070 was isolated from nickel-rich soil collected near Koniambo massif, New Caledonia, using the invasive legume trap host Mimosa pudica. STM 6070 is a heavy metal-tolerant strain that is highly effective at fixing nitrogen with M. pudica. Here we have provided an updated taxonomy for STM 6070 and described salient features of the annotated genome, focusing on heavy metal resistance (HMR) loci and heavy metal efflux (HME) systems.Results: The 6,771,773 bp high-quality-draft g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
(15 reference statements)
0
4
0
1
Order By: Relevance
“…Together, the MRGs listed in Table 1 contribute to resistance to copper, silver, magnesium, cobalt, mercury, molybdenum, arsenic, zinc, cadmium, iron, antimony and nickel. Many species of Cupriavidus including C. pauculus [76,77], C. metallidurans [78,79], C. gilardii [80], C. campinensis [81] and C. neocaledonicus [82] are considered to be metal resistant. Many of these genes confer resistance to metals by means of intracellular metal sequestration to facilitate export, as in the case of CopZ with Cu + ions [83], Ag + and Cd 2+ ions [84].…”
Section: Discussionmentioning
confidence: 99%
“…Together, the MRGs listed in Table 1 contribute to resistance to copper, silver, magnesium, cobalt, mercury, molybdenum, arsenic, zinc, cadmium, iron, antimony and nickel. Many species of Cupriavidus including C. pauculus [76,77], C. metallidurans [78,79], C. gilardii [80], C. campinensis [81] and C. neocaledonicus [82] are considered to be metal resistant. Many of these genes confer resistance to metals by means of intracellular metal sequestration to facilitate export, as in the case of CopZ with Cu + ions [83], Ag + and Cd 2+ ions [84].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison between the genomes of UYPR2.512, C . taiwanensis LMG19424 and the recently proposed Cupriavidus neocaledonicus STM6070 has shown that while LMG19424 and STM6070 had almost identical Sym plasmids, the UYPR2.512 strain would harbour a divergent Sym plasmid (Clerissi et al ., 2018; Klonowska et al ., 2020). However, nod , nif , fix and fdx genes are highly conserved between the analysed genomes of rhizobial Cupriavidus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cupriavidus rhizobia have been found associated with members of the Mimosoid clade both in species occurring in their native habitats and as invasive species (Barrett and Parker, 2006;dos Reis et al, 2010;Liu et al, 2012;Taulé et al, 2012;Gehlot et al, 2013;Platero et al, 2016). Nowadays there are two recognized Cupriavidus species containing rhizobia strains: Cupriavidus taiwanensis (Chen et al, 2001;Moulin et al, 2001;Vandamme and Coenye, 2004) and Cupriavidus necator (da Silva et al, 2012), though there is increasing evidence for the existence of additional rhizobia containing species (Platero et al, 2016;Klonowska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Branco y Morais (61) establecen la importancia de los genes chrC y chrF para evitar la acumulación de especies reactivas de oxígeno (ROS) en las células sometidas a estrés por cromato; además, establecen una gran similitud entre el producto génico de chrC de la cepa 5bvl1 con la Fe-SOD (ChrC) de C. metallidurans CH34. En contraste, el producto génico de chrF de Cupriavidus neocaledonicus STM 6070 aislada de un suelo rico en níquel y el producto del gen chrI de C. metallidurans CH34 han sido identificados como represores del operón chr (62,63). Sin embargo, esto difiere de otro estudio, en el cual identifican que chrF codifica para un superóxido dismutasa (Mn-SOD) (61).…”
Section: Determinantes De Resistencia Al Cromato Y Sus Mecanismosunclassified